ANALISIS LOKASI IBUKOTA KERAJAAN SRIWIJAYA ABAD 7-8 M - Najuah Najuah; Lulu Luciana Sinurat; Khalishatun Zahra; Akhila Ardianti Nasution; Cahaya Purnama Sari (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
Srivijaya Kingdom is one of the strong maritime kingdoms on the island of Sumatra and has a lot of influence in the archipelago with a wide area of authority. However, in fact the Srivijaya Kingdom was actually the